FAKTOR-FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PADA PERUSAHAAN MANUFAKTUR - ARIES VERONICA (Program Studi Magister Manajemen FE Unsri, 2015)
This study was conducted to examine the probability of the effect of profitability, liquidity, firm size (Size), leverage, and the life of the bonds against bond ratings on companies listed in the Indonesia Stock Exchange. Sample of companies used in this study were 29 companies listed on the Stock Exchange during 2011-2013. Data analysis technique used is the multiple logistic regression analysis and hypothesis testing using the Chi-square test (test simultaneously) and the Wald test (partial test) .From the summary model results showed a value of 0.555 or 55.5%, this means donations of variable profitability, liquidity, firm size (size), leverage, and the life of the bonds to the bond rating of 55.5%, while the remaining 44.5% is explained by other factors not diteliti.Chi-square test (test simultaneously) shows Chi-square count (39.731)> Chi-Square table (104.14) and the significance of the Chi-Square value of 0.000 <0.05, then the probability of profitability, liquidity, firm size (size), leverage, and the life of the bonds simultaneously influence obligasi.Uji ranked Wald (partial test) show (1) a significance level of liquidity of 0.000 <0.05, meaning that the probability of liquidity significant effect on bond ratings (2) Size significance level of 0.000 <0.05, meaning that the probability of a significant effect Size the bond rating (3) the level of significance of the life of the bonds of 0.000 <0.05, meaning that the probability of bond age significantly influence the ranking obligasi. Before buying bonds, investors should have sufficient information and knowledge about bonds as well as good business sense to be able to analyze factors Factors that affect bond ratings.